Analisis Kandungan Logam Kadmium (Cd) COD dan BOD dalam Limbah Air Sungai Sleng dengan Menggunakan Arang Aktif dari Kulit Kopi - Amelia, Tri Widya Sasnita; Iryani, A. Sry (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
Heavy metals such as Cadmium (Cd) are pollutants that are very dangerous to life because they are toxic, cannot be degraded, and are easily absorbed into the soil. Metal pollution is very dangerous because it can damage and cause serious global problems. The content of heavy metals such as Cd can damage the environment and waters in the area. The presence of heavy metals in large quantities can affect ecological and biological aspects. This study analyzed the effectiveness of activated charcoal from coffee husks in removing cadmium (Cd) from wastewater from the Sleng River. Wastewater from the Sleng River was contaminated with Cd with a concentration of 0.0521 mg/L, five times higher than the permitted threshold of 0.0100 mg/L. The author made activated charcoal from coffee husks through carbonization and activation using ZnCl₂. The results showed that activated charcoal from coffee husks was effective in reducing Cd concentration, with an optimum mass of 150 mg for both treatments (with and without activation). For COD, unactivated charcoal was more effective (reducing it from 134.3 mg/L to 86.9 mg/L). Meanwhile, for BOD, activated charcoal showed better results (reducing it from 20.4 mg/L to 16.6 mg/L).